Okay,
so first you gotta know that cos(90-x) is equal to sinx and sin(90-x) is equal to cosx!!
Now all you gotta do is replace the cos(90-x) to sinx in the numerator and sin(90-x) to cosx in the denomenator inorder to make the numerator all into sin and denomenator all into cos.
After that, open up the brackets and solve...
At the end you'll hopefully get something like this :( 1+sin90 ÷ 1+cos90 )
And since sin90 is 1 (put it in the calculator!) and cos90 is 0, you'll get 2÷1 which is equals to 2!!
Hope this helped! :)
Answer:
Yes
Step-by-step explanation:
3(5+1)=3(5)+3
15+3=15+3
18=18
Answer:
18
Step-by-step explanation:
Hey!
so first distribute the 5 to x + 4
5x+20 = 2x + 20 + 2x
combine 2x and 2x
5x+20 = 4x + 20
Now you want the constant and variable on different sides so subtract 4x to the other side
5x - 4x + 20 = 20
1x + 20 = 20
now subtract the 20 on the 1x + 20 side to the other side
1x = 0
divide by 1
0 divided by anything is 0
So x = 0
Hope this helps!
Answer:
3/4
Step-by-step explanation:
12/16 can be simplified just divide by 4
hoped this helped